Evidence in Civil Law - Spain - Mallandrich Miret, Núria (Institute for Local Self-Government and Public Procurement Maribor, 2015)
This work presumes to be an introduction for the foreign reader to Spanish regulations in regard to evidence. It has been structured following a classic design in the Spanish academic literature with the aim to approach the reader to the Spanish legal way of thinking. With the same goal it a starting Chapter that analyzes the different principles that lead Spanish Civil Procedure has been included.
English
Keywords: Political structure & processes; civil procedure; spain; ordinary proceedings; means of proof; fundamental principles of the procedure; evidence; oral trials; Defendant; Expert witness; Hague Conventions of 1899 and 1907; Legal doctrine; Letters rogatory; Plaintiff; Preliminary hearing